Genetic Association of Interleukin 33/ST2 Polymorphisms With Behcet’s Uveitis - Pei, Minghang; Liu, Xinshu; Yang, Peizeng; Zhao, Chan; Gao, Fei; Qu, Yi; Liang, Anyi; Xiao, Junyan; Zhang, Meifen (Frontiers in Immunology, 2021)
Interleukin (IL)33, a member of the IL1 superfamily, functions as a nuclear factor and mediates biological effects by interacting with the ST2 receptor. Recent studies have described IL33 as an emerging pro-inflammatory cytokine in the immune system, and IL33/ST2 gene polymorphisms have been implicated in the pathogenesis of various immune diseases. However, the underlying mechanisms of IL33/ST2 in Behcet's disease (BD) remain to be defined. Here, we investigated the association between IL33/ST2 gene polymorphisms and BD in 585 BD uveitis (BDU) patients and 834 healthy controls using Agena MassARRAY iPLEX platform . We found that rs3821204 was associated with the development of BDU. Moreover, the frequency of rs2210463 G allele was lower in patients with genital involvement. Association analysis revealed a much greater genetic difference between complete-type and incomplete-type BD groups, including 3 SNPs (rs7044343, rs1048274, and rs2210463). Our findings suggest that IL33/ST2 gene polymorphisms are involved in the pathogenesis of BDU. Different genetic backgrounds may exist in complete-type and incomplete-type BD patients.